Преобразователь давления с частотным выходом на основе однопереходных тензотранзисторов - Babichev, G. G.; Gavrilyuk, G. I.; Zinchenko, E. A.; Kozlovsky, S. I.; Romanov, V. A.; Sharan, N. N. (PE "Politekhperiodika", Book and Journal Publishers, 2004)
The operating principle of single-junction strain transistors is discussed. It is shown that the strain sensitivity of a single-junction transistor with a controlled p-n junction is an order of magnitude higher than that of a simple single-junction transistor. It is concluded that the proposed pressure transducer with a frequency output is of practical interest for the creation of devices with increased requirements for noise immunity and measurement accuracy of the information signal.